(untitled) (Международный научный журнал «Инженер», 2026)
This article analyzes the importance, effectiveness, and future development prospects of rainwater harvesting and recycling technologies in Uzbekistan. In the context of limited water resources and climate change in the country, rainwater harvesting is an important factor in alleviating water supply problems. The study provides information on various technical solutions - water harvesting areas, filtration systems, and storage facilities, and assesses their environmental and economic effectiveness. It also discusses the possibilities of widespread implementation of these technologies in agriculture and the lives of the population and the problems associated with them. In conclusion, it is necessary to strengthen the regulatory and legal framework, technologies appropriate to local conditions, and public awareness campaigns to expand the use of rainwater in Uzbekistan.